Written emotional expression in schools: Processing psychological and emotional stress through narrative writing. - Sassu, Kari A.; Bray, Melissa A.; Gelbar, Nicholas; Kerzner, Tiffany P. (Promoting mind–body health in schools: Interventions for mental health professionals., 2020)
tex.ids: sassuWrittenEmotionalExpression2020a
Keywords: dept.csp

Psychologically based therapies to improve lung functioning in students with asthma. - Maykel, Cheryl; Bray, Melissa A; Gelbar, Nicholas W; Caterino, Linda C; Avitia, Maria J; Sassu, Kari; Root, Melissa M (International journal of school and educational psychology, 2016)
Asthma is a common, chronic respiratory disease that can be costly to both society and the individual. In addition to increased absenteeism, children with asthma may also be at a greater risk for developing comorbid anxiety and depression. Various complementary psychological treatments have been effective at reducing both asthmatic symptoms and psychological distress. Although the research in the area of mind-body treatments as it pertains specifically to persons with asthma is still developing, this article will describe several promising alternative treatment methods, many of which have already been, or could be easily be applied for use in a school setting. © 2016, © 2016 International School Psychology Association.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/039-833-211-583-544 tex.type: [object Object]
Keywords: art therapy; asthma; biofeedback; dept.csp; hypnosis; mind-body; mindfulness; music therapy; relaxation and guided imagery; school-based interventions; written emotional expression; yoga

Interdependent group contingency to promote physical activity in children - Foote, Catherine; Bray, Melissa A.; Kehle, Thomas J.; VanHeest, Jaci L.; Gelbar, Nicholas W.; Byer-Alcorace, Gabriel; Maykel, Cheryl; DeBiase, Emily (Canadian Journal of School Psychology, 2017)
As the number of children affected by obesity increases in the United States, it is necessary to intervene with preventive and intervention techniques that will enact change. Because children spend a significant amount of their time in school, it is of particular interest to target strategies during the school day. Given the recommendations for the total duration and intensity of physical activity children should participate in, recess period is a means of acquiring a portion of this daily recommendation. Contingent reinforcement is a technique that is consistently used in schools to promote behavior change. One of these techniques, group contingencies, has repeatedly been shown to increase desired behavior and decrease inappropriate behavior in schools. In the present study, a multiple baseline design was utilized to investigate the use of interdependent group contingencies in physical activity performance during recess, as measured by pedometers, with one class from each of the third, fourth, and fifth grades at an elementary school. Some of the variability existed in gender- and body mass index-specific (BMI) subgroups, in regard to the effectiveness of the intervention and continued maintenance of increased physical activity levels, following the removal of the intervention. However, the overall results support the use of an interdependent group contingency intervention to increase the amount of physical activity students engaged in during recess.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-793-861-482-608 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.csp; exercise; obesity; school-based treatment